Design and implementation of an android mobile application prototype for the University of the Philippines College of Engineering Library - Santos, Patcheska Dewi R.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
Technology has evolved greatly in a short span of time. Gadgets and all other means that can provide easier and faster access are everywhere. People always look for new and advanced developments in terms of technological capability. As everything gets diverse, libraries will not be able to fully provide the information and access that the users need if they will not be able to keep up with the rapid pace of technological developments. Mobile phones have also found their way in libraries, providing new avenues for providing services.
The study aims to establish conventions for the design of a mobile application with the advantages that come with it mainly to provide easier and faster access to the library to promote its offerings. Also, the study aims to serve as a model for the design and implementation of a mobile application for libraries in general.
Development of the mobile application began with determining the most library website features that the users visit or use through an evaluation survey conducted on the users of the UP College of Engineering Library I and II. Evaluation was conducted using Systematized Random Sampling as well as personal interviews after the users have tested the mobile application. Findings of the study indicated that the mobile application was sufficient for the purpose it was built for. Through the study, it was determined that the Online Public Access Catalog is an essential feature of the mobile library application, the respondents expected basic library services to be available on the application, and making the mobile application suitable to any operating system is necessary to make it available for non-android users.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines (Diliman) College of Engineering; G1 (Smartphones).